Do You Always Choose What You Like? Subtle Social Cues Increase Preference-Choice Consistency among Japanese But Not among Americans - Uchida, Yukiko; Savani, Krishna; Hitokoto, Hidefumi; Kaino, Koichi (Frontiers in Psychology, 2017)
Previous research has suggested that the stability of a person’s sense of self differs across cultures: in the U.S., a person’s sense of self is understood as stable regardless of the social contexts, whereas in Japan, it is understood as primarily activated within specific social contexts. We examined the implications of these cultural differences for preference-choice consistencies, that is for people’s tendency to make choices that are consistent with their preferences. We found that Japanese were less likely than Americans to make choices based on their personal preferences. Further, we asked under what conditions might Japanese exhibit greater preference-choice consistency. Consistent with research that in Japanese culture the self is primarily conceptualized and activated with reference to the social context, we found that subtle social cues (schematic representations of human faces) increased preference-choice consistency among Japanese, but not among Americans. These findings highlight that choices do not reveal preferences to the same extent in all cultures, and that the extent to which choices reveal preferences depends on the social context.